Frantz Fanon as the theorist of the political subject: An essay - Samaddar, Ranabir (Hagar: Studies in Society and Culture, 2010)
In political and historical literature, decolonization is seen mostly as a process. Therefore, the question is forgotten: who decolonizes? Or what is decolonized? The issue of the subject-once colonized and now to be decolonized-is thus absent. A question needs to be raised in the necessary discussion: Are we speaking of the nation now being decolonized, or are we thinking of the political subject beyond the nationalist framework? This is not a purely speculative question. How we look at nationalist power and political strategies is an intrinsic part of the discussion. Besides several other reasons, this will be the justification to study Fanon once more.